Experimental analysis of basic mechanical properties of concrete upon replacement with silica fume and steel slag. Issue 1 (November 2021) - Verma, Nitin; Singh, Balwinder
Abstract: The prime aim in this paper is to find out the effect of Silica Fume and Steel Slag replacements for cement and fine aggregate respectively in the concrete matrix. The research included replacement of constant percentage of silica fume i.e. 10% with cement and varying percentages of steel slag replacements viz. 40%, 45%, 50% and 55% with fine aggregates. It was found from the experimental investigations that optimum results for strength in compression, flexure and split case for concrete were established on 10% of silica fume replacement for steel slag and 50% replacement of steel slag with sand.